Evolution in Scientific Production in the Area of Vegetarian Nutrition, 1907-2013. - Julio, Cesar Acosta-Navarro; Adriana, Midori Oki; Luiza, Antoniazzi Gomes de Gouveia; Valeria, Hong; Maria, Aparecida Carlos Bonfim; Raul, D. Santos (International Journal of Nutrition, 2015)
The objective is to evaluate the scientific evolution of articles about vegetarian nutrition. We analyzed the publication of articles of vegetarian nutrition, using the key term ‘vegetarian’ in the National Institutes of Health MEDLINE bibliographic database between 1907 and 2013. We quantified the number of articles in vegetarian nutrition by 5–y time periods, and we classified the kind of journals, the affiliation of the first author, the origin of the study population and the type of articles. The number of articles found in MEDLINE is 3256. The publication rate of vegetarian articles increased steadily, except in periods of 2006-2010 and 2011-2013, and this was explained because the application of “embargo period” for the some publishers. Non-nutrition journals have published more articles on vegetarian nutrition for all periods. It is observed that after 1960 the articles on vegetarian nutrition are proportionately greater than the total published, except in the years 2007, 2008, 2011, 2012 and 2013. The majority of authors were located in Europe (41.7%), followed by North America (26.8%), Asia (16.1%) and Latin America (1.4%). The origin of the study population presented a similar trend being highest in Europe and lowest in Latin America. Original research and review articles represent 52.5% and 20.2% of all publications respectively. We noticed a marked increase in the publication of articles of vegetarian nutrition over the years in absolute and relative terms meaning a growing interest by publication type.
Keywords: Diet; Vegetarian; MEDLINE; Bibliometric Indicators; articles